Optimized Sugar Beet Seedling Growth via Coordinated Photosynthate Allocation and N Assimilation Regulation - Kehua Chen; Mingyue Chu; Qing Bai; Lingqing Xu; Yuanhang Zhou; Xiaodong Li; Hao Wang; Wang Xing; Dali Liu (Agriculture, 2025)
Sugar beet is a nitrogen (N)-sensitive crop, and its N regulation and utilization are critical for enhancing productivity. Sugar beet seedlings at the two-true-leaf-pair stage were hydroponically grown in an artificial climate chamber. Leaves and roots from three seedlings per treatment were sampled at 10, 20, 25, and 30 days after exposure to N treatments (N5: 5 mmol/L, N10: 10 mmol/L, N15: 15 mmol/L, and N20: 20 mmol/L) to assess the effects of N supply level on growth, photosynthesis, and carbon and nitrogen metabolism. The results revealed a time-dependent dynamics in beet biomass accumulation, with N20 inducing chlorosis and necrosis symptoms by 10 days post-treatment (DPT), resulting in the lowest biomass. While N15 significantly promoted root biomass by 30 DPT, showing a 23.70% (root dry weight, RDW) increase over N20; chlorophyll content and gas exchange parameters-net photosynthetic rate (Pn), stomatal conductance (Gs), transpiration rate (Tr) exhibited significant N dependence, with N15 maintaining high chlorophyll level (0.78 mg/g) and photosynthetic rate (220.33 μmol/(m2·s). Nitrogen assimilation, as indicated by glutamine synthetase and glutamate synthetase activity (GS and GOGAT), was stronger under N15, promoting amino acid synthesis and root growth, whereas N20 inhibited enzyme activity. Carbon metabolism analysis revealed that N15-driven sucrose synthesis significantly increased root sucrose content, sucrose phosphate synthase and sucrose synthase activity (SPS and SS), optimizing source–sink allocation. Correlation analysis showed a positive relationship between leaf and root biomass (r = 0.91), and root sucrose content was positively correlated with GOGAT activity (r = 0.90), emphasizing the synergistic regulation of C/N metabolism. On the contrary, N20 led to disrupted C/N metabolic homeostasis, inhibited enzyme activity, and C/N distribution. These results indicated that the photosynthetic output, enzyme efficiency, and sucrose distribution were coordinated by nitrogen optimization, and the growth of sugar beet seedlings was optimized.